2018
DOI: 10.1016/j.jpainsymman.2018.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Hyoscine Butylbromide for the Management of Death Rattle: Sooner Rather Than Later

Abstract: The prophylactic use of HB is an efficient method to prevent DR, whereas the late administration produces a limited response, confirming data from traditional studies performed with anticholinergics. This could be considered a new paradigm to manage a difficult and dramatic sign, such as DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 15 publications
(18 reference statements)
0
27
0
Order By: Relevance
“…Across all categories, the tool most frequently employed was the original Richmond Agitation-Sedation Scale (RASS) or its modified versions (n = 17). 10,21,35,51,[53][54][55]64,70,72,73,77,84,86,87,91,93 To assess level of consciousness Three of the ad hoc measures were modified versions of the existing tools: the Glasgow Coma Scale (GCS), 32,33 RASS 19,35 and Riker Sedation-Agitation Scale. 23,39 All other ad hoc measures comprised unique tools.…”
Section: Description Of Identified Measuresmentioning
confidence: 99%
“…Across all categories, the tool most frequently employed was the original Richmond Agitation-Sedation Scale (RASS) or its modified versions (n = 17). 10,21,35,51,[53][54][55]64,70,72,73,77,84,86,87,91,93 To assess level of consciousness Three of the ad hoc measures were modified versions of the existing tools: the Glasgow Coma Scale (GCS), 32,33 RASS 19,35 and Riker Sedation-Agitation Scale. 23,39 All other ad hoc measures comprised unique tools.…”
Section: Description Of Identified Measuresmentioning
confidence: 99%
“…Respiratory secretion, especially death rattle, and changes in respiratory patterns (eg, Cheyne-Stokes breathing and respiration with mandibular movement) are often seen during the last days of life 8 23 24. These may lead to distress in families; while clinicians have traditionally believed there is no patient distress caused by death rattle and changes in respiratory patterns developed in the context of declining consciousness, whether the patient perceives distress remains controversial 76–78…”
Section: Current Evidence Supporting Treatment For Terminal Breathlesmentioning
confidence: 99%
“…Anticholinergics have been used to reduce respiratory secretion; however, systematic reviews revealed no additional benefit of medications or non-pharmacological treatments compared with a placebo 79 80. A prophylactic use of anticholinergics has recently been proposed to prevent death rattle but such a suggestion is without sufficient evidence of benefit 77. Therefore, the evidence for pharmacological management to reduce secretions is controversial at present.…”
Section: Current Evidence Supporting Treatment For Terminal Breathlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized controlled trial conducted in Belgium, the subcutaneous administration of atropine, scopolamine butylbromide, and scopolamine hydrobromide showed an improvement of approximately 40% on a pre-post basis; no significant difference between the drugs was reported [33]. Recently, the prophylactic administration of hyoscine butylbromide was shown to effectively prevent the death rattle [34]. However, because a randomized controlled study found that atropine was not superior to a placebo control, anticholinergic drugs are not widely recognized as the gold standard treatment [35].…”
Section: Increased Bronchial Secretionsmentioning
confidence: 99%